Controlled and Secure Access to Promote the Industrial Internet of Things - Marco A. Marquez; Reyes S. Herrera; Andres Mejias; Francisco Esquembre; Jose M. Andujar (IEEE Access, 2018)
Internet of Things (IoT) aims at facilitating access to all devices that are connected to the internet, both wired and wireless. This scenario can initially seem interesting. Nevertheless, it has a lack of privacy and danger of malicious interaction with the devices. Therefore, IoT, as it stands, is not suitable for companies to make their data and devices accessible through the internet, since they could find an untidy cloud, made up of devices without the necessary control of use. This paper proposes the use of the cloud computing advantages to develop a secure access global system based on a cloud. The company will decide the controlled access to the chosen devices and data, both by employees and external people. The developed system can be used from different scenarios such as: a public cloud; an Infrastructure as a Service (IaaS); and a private cloud. To illustrate the operation of the developed system, a representative network of heterogeneous multiprotocol devices has been designed.